The Effects of High Cushioned Versus Minimal Cushioned Shoes on Dynamic Postural Stability of Older Adults During Obstacle Crossing - Naghdlou, Sara (Université d'Ottawa / University of Ottawa, 2021)
Footwear can affect postural stability in individuals, particularly in elderly people. Aging-related decline in postural stability, particularly in the mediolateral (ML) direction, is a risk factor for falls and fall-related injuries among older adults. This study aimed to investigate the effects of high cushioned and minimal shoes on dynamic postural stability in ML during obstacle crossing in defined older and younger adults. Six healthy older adults (50–60 years old, body weight: 74.8 kg, body height: 168.0 cm) and six healthy younger adults (18–32 years old, body weight: 73.8 kg, body height: 174.8 cm) participated in the study. A Vicon motion analysis system with 10 optical cameras was used to capture the obstacle (20 cm height) crossing motion of the participants at 200 Hz, and ground reaction forces of obstacle crossing were collected at 1000 Hz. Motion data of obstacle crossing were collected at three shoe conditions, namely, minimal shoe, high cushioned shoe and barefoot (control). Data from five trials of obstacle crossing for each shoe condition were processed using Vicon Nexus software 2.11.0 and Matlab R2013b. Displacement and velocity of centre of mass (COM) in the ML direction, COM–centre of pressure (COP) ML separation, step length, step velocity, toe clearance, pre-horizontal distance, hip flexion angle and hip abduction angle during obstacle crossing were examined. One-way ANOVA with pairwise analysis showed that toe clearance was significantly larger in the high cushioned shoe conditions than in the minimal shoe and barefoot conditions in older adults (high cushioned shoes vs. barefoot: p = 0.019; cushioned shoes vs. minimal shoes: p = 0.031) and younger adults (high cushioned shoes vs. barefoot: p = 0.016; high cushioned shoes vs. minimal shoes: p = 0.000). No significant difference in the measures was found between the minimal shoe and barefoot conditions in each group. Compared with older adults, younger adults showed significantly larger step length in barefoot condition (p = 0.000) and minimal shoe (p = 0.016). Independent t-test for examination of the significant difference of the means of each measure when the shoe condition was changed showed that only step length and step velocity were significantly different between older and younger adults. When the shoe condition was changed from minimal shoe or barefoot to high cushioned shoe, older adults showed significantly bigger change in step velocity (10.04 ± 4.39 cm/s for older; 1.87 ± 0.81 cm/s for younger; p = 0.034) and step length (14.26 ± 6.99 cm for older; 2.086 ± 1.13 cm for younger; p = 0.041) than younger adults. This result indicates that older adults had 23% greater total range of step length and 12% greater total range of step velocity compared with younger adults when shoe condition changed. Moreover, older adults showed 16% smaller total range in their maximal COM-COP ML separations than younger adults when shoe condition changed. It is concluded that high cushioned shoes can influence dynamic postural stability in the ML direction during obstacle crossing in younger and older adults. The minimal shoe and barefoot conditions did not show significant influence on postural stability in the ML direction during obstacle crossing in older and younger adults. The minimal shoe on dynamic postural stability in the ML direction is not significant. Age differences in dynamic postural stability in the ML direction during obstacle crossing were found at the same shoe conditions. Moreover, when shoe condition was changed, shoe cushioning conditions affected postural stability to a larger extent in older adults compared with younger adults. The high cushioned shoe led to a more challenged postural stability in adults aged 50 to 60 than younger adults aged 18 to 32.
Keywords: Postural stability; Cushioning; Older adults; Shoes; COM; COP; Obstacle crossing